Louise Nevelson : Black, White & Gold. (New York : The Pace Gallery, 1992)
The catalogue/announcement for an exhibition of sculptures by Louise Nevelson, held at The Pace Gallery, October 23 through November 28, 1992. One of the reproductions of her sculptures is printed in silver ink, another in gold; the whole presentation is ribbon-tied with a silver-printed portrait of Nevelson on the front. 6 pages with 3 die-cut printed pop-ups; 9 x 9 inches.
Louise Nevelson : Black, White & Gold, The Pace Gallery, New York, October 23 - November 28, 1992
Engels
kunstcatalogus
Keywords: Nevelson, Louise